ScFOS supplemented follow-on formula in healthy infants: Impact on vaccine specific faecal secretory IGA response, faecal bifidobacteria, growth and digestive tolerance. Issue 2 (April 2015) - Ripoll, Christophe; Chappuis, Eric; Respondek, Frédérique; Wagner, Anne; Gottrand, Frédéric
Abstract: Objectives: Few studies have assessed efficacy and safety of prebiotics in infants at the time of diversification. We investigated the beneficial effects of a follow-on milk formula supplemented with short-chain fructo-oligosaccharides (scFOS) in healthy infants after 4 months of age. Subjects/methods: 75 formula-fed healthy infants were included at the age of 4 months in a randomized, controlled, double blind study and received either a placebo or scFOS supplemented formula for six months. Faecal poliovirus sIgA after vaccination and bifidobacteria concentration, height, weight and digestive tolerance were monitored. Results: After 1 and 2 months of supplementation, no significant difference was observed between the groups for the evolution of poliovirus sIgA concentration compared to baseline. A significant increase in bifidobacteria count was observed after 1 month of ScFOS supplementation, but this difference was no longer significant after 2 months. Breastfeeding history of infants was shown to have an impact on faecal bifidobacteria evolution. Tolerance and growth parameters were similar in the 2 groups. Conclusions: A follow-on milk formula supplemented with scFOS modulates intestinal microbiota via an increase of faecal bifidobacteria concentration, while no effect on sIgA concentrations could be demonstrated. scFOS addition elicited normal digestive tolerance and normal growth suggesting it can be used safely at 5 g/L in infants after 4 months of age. Highlights: Intestinal microbiota development in early life plays a crucial role in immune response. Short-chain fructo-oligosaccharides (scFOS) combined with other oligosaccharides improve immune response in infants formulas. We evaluated scFOS in follow-on milk formula on immune response to poliovirus vaccination in previously- and never breastfed infants. scFOS supplemented formula was well tolerated and associated to normal growth. scFOS supplemented formula did not elicit improved response to the vaccine. scFOS formula was bifidogenic only in never breastfed infants and on the short term.